Genetic diversity of piracanjuba used in stock enhancement programs with microsatellite markers - Rodriguez-Rodriguez, Maria del Pilar; Lopera-Barrero, Nelson Mauricio; Ribeiro, Ricardo Pereira; Povh, Jayme Aparecido; Vargas, Lauro; Sirol, Rodolfo Nardez; Jacometo, Carolina Bespalhok (Pesquisa Agropecuária Brasileira, 2010)
The objective of this work was to estimate the genetic diversity of a Brycon orbignyanus lot used in stock enhancement programs, using microsatellite markers. Samples of 44 broodstocks, 70 larvae and 69 fingerlings, were analyzed with amplification of five loci described for Brycon opalinus. The number of alleles, the observed (Ho) and expected (He) heterozygosity, Shannon index (IS), Nei’s genetic diversity (DGN), the inbreeding coefficient (Fis), distance (DG) and genetic identity (IG), the effective number of alleles, the test of Hardy-Weinberg equilibrium (EHW) and the linkage disequilibrium were calculated. Broodstocks and offspring had a similar number of alleles at the tested loci. Ho average, IS, DGN, DG and IG showed that there is less genetic distance between parental and larvae and a decrease of genetic variability in the fingerlings. Deviations in the EHW and disequilibrium ligation were observed in six pairs of loci. Inbreeding coefficient showed excess of heterozygotes in parental and larvae and heterozygote deficiencies in fingerlings. The broodstock is in process of allele losses and the genetic variability decreased between larva and fingerling stages.